Guide to computer forensics and investigations - Nelson, Bill; Phillips, Amelia; Steuart, Christopher (Course Technology, 2010)
Helps learners master the skills necessary to launch and complete a successful computer investigation. This resource guides them through conducting a high-tech investigation, from acquiring digital evidence to reporting its findings. It features free downloads of the forensic software, so readers can become familiar with the tools of the trade.